Pemanfaatan Lingkungan Sekolah Untuk Meningkatkan Keterampilan Menulis Deskripsi Siswa Kelas VI Sekolah Dasar - Saroi, Umi; Rochmiyati, Siti (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
The background to this research is that there are difficulties among class VI students at Jagamangsan 2 State Elementary School in writing descriptive texts, which is indicated by the percentage of students who have not yet completed the KKM of 70 as much as 75%. The aim of this research is to describe the learning outcomes of class VI students in Indonesian language lessons in writing descriptions that utilize the school environment. As well as describing obstacles that arise during learning activities and how to overcome them. This research uses a PTK design. The subjects of this research were teachers and students of class VI at SD Negeri Jagamangsan 2 Berbah Sleman, totaling 24 students. Data collection techniques use observation and tests. The research results showed that the average percentage of learning implementation in cycle I reached 80.31%, while in cycle II it reached 86.54%. Student learning outcomes showed classical completeness in cycle I of 62.50% and increased in cycle II of 79.17%. Based on the results of these data, it can be concluded that utilizing the school environment can improve the description writing skills of class VI students at SD Negeri Jagamangsan 2 Berbah Sleman.